Impact of Net Neutrality and the Open Internet Order on Security and Privacy in Education (Journal of The Colloquium for Information Systems Security Education, 2015)
The Open Internet Order is the result of a multi-year Federal Communications Commission (FCC) effort to address the challenge of net neutrality. This paper analyzes the impact of the Open Internet Order on universities in terms of standard operating procedures, costs, security, privacy, and quality of education. This paper only considers the US regulations that affect Internet access and their implications on universities. These regulations may also have wide-ranging international implications, which are not considered here.
Keywords: Education; FCC; Internet; Net Neutrality; Open Internet Order; Privacy; Regulation; Section 706; Security; Title II; University